PENGEMBANGAN WEB PEMBELAJARAN MATEMATIKA MATERI ARITMATIKA SOSIAL - Mukhammad Danisworo; Yus Mochamad Cholily; Alfiani Athma Putri Rosyadi (Program Studi Pendidikan Matematika, 2019)
This study aims to develop a mathematics learning for social arithmetic material and see student responses to the mathematics learning web for social arithmetic material. The research method used is and Development (R & D) which starts from determining potential problems, data collection, product design, design validation, design revisions, product trials, and product revisions. The subjects in this study were VII grade students at MTs Muhammadiyah 1 Malang and 6 selected students with categories 2 high, 2 medium, and 2 low from the results of social arithmetic tests that had been done. The results showed that: 1) the learning web that had been developed gets a score of 3.55 which means the learning web is valid; 2) student responses to the learning web gained a score 3.65 (high).